2013
DOI: 10.1140/epjp/i2013-13022-4
|View full text |Cite
|
Sign up to set email alerts
|

On CCC-predicted concentric low-variance circles in the CMB sky

Abstract: A new analysis of the CMB, using WMAP data, supports earlier indications of non-Gaussian features of concentric circles of low temperature variance. Conformal cyclic cosmology (CCC) predicts such features from supermassive black-hole encounters in an aeon preceding our Big Bang. The significance of individual low-variance circles in the true data has been disputed; yet a recent independent analysis has confirmed CCC's expectation that CMB circles have a non-Gaussian temperature distribution. Here we examine co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
115
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 34 publications
6
115
0
Order By: Relevance
“…Each such black-hole encounter would provide a circular "ripple" in the CMB around which the temperature variance would be rather low, and the average temperature would be raised or lowered slightly (raised for particularly distant sources and lowered for relatively near ones). There appears to be some definite evidence that such signals are actually present in our CMB, as revealed in the WMAP data; see Gurzadyan and Penrose [3] and Meissner et al [6]). It is to be hoped that when the somewhat more precise data from the Planck satellite becomes publically available, it will be possible to ascertain whether or not these findings are confirmed at this more refined level.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Each such black-hole encounter would provide a circular "ripple" in the CMB around which the temperature variance would be rather low, and the average temperature would be raised or lowered slightly (raised for particularly distant sources and lowered for relatively near ones). There appears to be some definite evidence that such signals are actually present in our CMB, as revealed in the WMAP data; see Gurzadyan and Penrose [3] and Meissner et al [6]). It is to be hoped that when the somewhat more precise data from the Planck satellite becomes publically available, it will be possible to ascertain whether or not these findings are confirmed at this more refined level.…”
supporting
confidence: 54%
“…We see that CCC provides a completely different picture of the physics that is appropriate at the Big Bang from that which has been suggested by current investigations into quantum gravity. According to CCC, the relevant physics can be studied by means of entirely classical equations, these being derived from a study of conformal invariance and, from a natural-looking assumption concerning the relation between the pre-and post-crossover conformal factors, as we pass from aeon to aeon (see Penrose [12], Appendix B and Gurzadyan and Penrose [3], Appendix A). Remarkably, in view of the viewpoint that has held for many decades that the Big Bang represents the ideal laboratory for examining the effects of quantum gravity, the picture presented by CCC is utterly different, where the classical dynamics of massless fields holds sway, instead.…”
mentioning
confidence: 99%
“…It is commonly taken for granted (with the notable exception of Gurzadyan & Penrose [5]) that the temperature distribution in the CMB is purely statistical being produced by the quantum fluctuations usually assumed to have taken place during inflation (as evolution of quantum fields in De Sitter space suggests). Therefore, it was very unexpected for us to find significant differences (with confidence level 99.7%) between the WMAP results and artificial maps (with the same power spectrum as the real WMAP maps) that we have created.…”
Section: Resultsmentioning
confidence: 99%
“…up to the maximum of 90 degrees), while assuming there is no inflation we found an upper limit of around 20 degrees. In this context it is worth noticing that the largest circles found in the study reported in [4] and [5] have angular radius about 16 degrees, [14].…”
Section: Now the Friedman Equation Is Jusṫmentioning
confidence: 99%
“…This radiation travels from one aeon to the next and perturbs the matter distribution early in the next aeon, which in turn produces circular perturbations in the observed CMB. In two recent articles [4], [5], he and Gurzadyan claim that these circles can be observed in the CMB as circles with significantly lower variance in the temperature. This claim is controversial and a number of authors have disagreed with the statistical significance of the findings of Penrose and Gurzadyan [6], [7], [8], [9].…”
mentioning
confidence: 99%